Bicarbonate-Hydrogen Peroxide System for Treating Dyeing Wastewater: Degradation of Organic Pollutants and Color Removal (2023)
: The textile industry is a global economic driving force; however, it is also one of the most polluting industries, with highly toxic effluents which are complex to treat due to the recalcitrant nature of some compounds present in these effluents. This research focuses on the removal of Chemical Oxygen Demand (COD), color, Total Organic Carbon (TOC), and Ammoniacal Nitrogen (N-NH3 ) on tannery wastewater treatment through an advanced oxidation process (AOPs) using sodium bicarbonate (NaHCO3 ), hydrogen peroxide (H2O2 ) and temperature using a central composite non-factorial design with a surface response using Statistica 7.0 software. All experiments used a 500 mL reactor with 300 mL of tannery wastewater from a company in Cúcuta, Colombia. The physicochemical characterization was done to determine the significant absorbance peaks about the color in the wavelengths between 297 and 669 nm. Statistical analysis found that the concentration of NaHCO3 affects the removal of color and N-NH3 ; however, it did not affect COD and TOC. The optimal process conditions for removing the different compounds under study were: NaHCO3 1 M, H2O2 2 M, and 60 ◦C, with efficiencies of 92.35%, 31.93%, 68.85%, and 35.5% N-NH3 , COD, color, and TOC respectively. It can be concluded that AOPs using H2O2 and NaHCO3 are recommended to remove color and N-NH3.